2012
DOI: 10.1364/oe.20.014663
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization approach for THz polaritonic metamaterials

Abstract: In this paper we discuss the fabrication and the electromagnetic (EM) characterization of anisotropic eutectic metamaterials, consisting of cylindrical polaritonic LiF rods embedded in either KCl or NaCl polaritonic host. The fabrication was performed using the eutectics directional solidification self-organization approach. For the EM characterization the specular reflectance at far infrared, between 3 THz and 11 THz, was measured and also calculated by numerically solving Maxwell equations, obtaining good ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…The HRS was selected because of its outstanding properties including its low bulk material absorption loss < 0.01 cm -1 from 0.1-1 THz and its stable refractive index n = 3.417 in the frequency range from 0.5-4.0 THz [22]. Materials with ENZ properties can be attained with metamaterials [24,25] or with naturally occurring materials [26][27][28]. In this work, ideal ENZ material is used first.…”
Section: Thz Pcf Configurationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HRS was selected because of its outstanding properties including its low bulk material absorption loss < 0.01 cm -1 from 0.1-1 THz and its stable refractive index n = 3.417 in the frequency range from 0.5-4.0 THz [22]. Materials with ENZ properties can be attained with metamaterials [24,25] or with naturally occurring materials [26][27][28]. In this work, ideal ENZ material is used first.…”
Section: Thz Pcf Configurationsmentioning
confidence: 99%
“…Consequently, some trade-offs had to be managed. It was found that high purity KCl [26] is a good candidate for the THz PCF with its ENZ crossover point near 6.3 THz. The investigated material for the optical PCF was AZO [27,28]; it has its ENZ crossover point at optical frequencies near 1556 nm.…”
Section: Realistic Thz and Optical Pcfsmentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth overview of this technique is given in chapter 4. The directional solidification of eutectics has been exploited to fabricate split-ring resonator-like structures [ 67 ] and polaritonic MMs for THz applications [ 68 ]. Recently, self-assembly on the short-range scale was also demonstrated by introducing defect states into liquid crystals [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples with rods or ribbons with transverse optical modes between 26 and 41 µm have been recently reported, [16] heavier halides shift them to longer wavelengths and eutectics of other compounds are still to be explored from this point of view. [11,12] Phononpolariton metamaterials [13][14][15][16] or nanoplasmonic structures [17] based on eutectics start to be studied, and more recently also www.advopticalmat.de Micropatterned metal-dielectric structures have been proposed for sensors from the visible (VIS) to the THz range; [1,2] complex patterned photonic structures are used and further studied as electromagnetic (EM) wave absorbers for light harvesting in photovoltaics, [3,4] or selective thermal emitters.…”
mentioning
confidence: 99%